Choreotherapy as a creative method of supporting the development of a person experiencing trauma - Inglot-Kulas, Joanna (Edukacja • Terapia • Opieka, 2024)
Dance, as a human’s product, is their unique body and soul language that enrolls into the original culture of a given society. The dancer’s movement reflects the human nature in a very distinctive manner, allowing it to show its individual face. Through dance, an individual is able to participate in educational experiences, which is particularly useful for therapy. Dance is an original and creative instrument that opens people’s souls and bodies to the beauty of musical movement. The aim of choreotherapy is to restore the overall functioning of the physical, mental, and emotional systems of individuals who are in good health, but also have deficiencies, disabilities, or experience trauma. It is an original and creative method of releasing a permanent psychomotor tension. The body that is an inflection of a man’s inside is the starting point for the therapy. The interaction with another person, the individual movements of participants, expression and improvisation to the beat of the music not only support positive communication and social relations, but also awareness of one’s own body and the occurring, often unconscious, difficult emotions. These also liberates one’s own creativity and freedom of use and interpretation of musical work.